Effects of different levels of organic chromium and selenomethionine cocktails in broilers - Jaewoo An; Younggwang Kim; Minho Song; Jungseok Choi; Hanjin Oh; Seyeon Chang; Dongcheol Song; Hyunah Cho; Sehyun Park; Kyeongho Jeon; Yunhwan Park; Gyutae Park; et al. (Journal of Animal Science and Technology, 2023)
Selenium (Se) is an essential trace mineral that plays an important role in physiological processes by regulating the antioxidant defense system and enhancing immunity. Chromium is an essential mineral involved in carbohydrate and lipid metabolism and also plays a role in maintaining normal insulin function. Based on these advantages, we hypothesized that the addition of selenomethionine (SeMet) and organic chromium (OC) to broiler diets would increase Se deposition, antioxidant capacity and immune response in meat. Therefore, this study analyzed the effects of OC and SeMet on growh performance, nutrients digestibility, blood profiles, intestinal morphology, meat quality characteristics, and taxonomic analysis of broilers. A total of 168 one-day-old broiler chicken (Arbor Acres) were randomly allotted to 3 groups based on the initial body weight of 37.33 ± 0.24 g with 7 replicate per 8 birds (mixed sex). The experiments period was 28 days. Dietary treatments were folloewd: Basal diets based on corn-soybean meal (CON), basal diet supplemented with 0.2 ppm OC and 0.2 ppm SeMet (CS4), and basal diet supplemented with 0.4 ppm OC and 0.4 ppm SeMet (CS8). Supplementation of OC and SeMet did not affect on growth performance, nutrient digestibility. However, CS8 supplementation increased in duodenum villus height and villus height : crypt depth, and increased in breast meat Se deposition. In addition, CS8 group showed higher uric acid and total antioxidant status than CON group. Taxonomic analysis at phylum level revealed that Proteobacteria and Firmicutes of CS4 and CS8 were lower than CON group. In genus level, the relative abundance of fecal Lactobacillus and Enterococcus of CS4 and CS8 groups were higher than CON group. In short, 0.4 ppm OC and 0.4 ppm SeMet supplementation to broiler diet supporitng positive gut microbiome change, also enhancing antioxidant capacity, and Se deposition in breast meat.